The roles of LncRNA CARMN in cancers: biomarker potential, therapeutic targeting, and immune response - Huafeng Liu; Xuewen Liu; Yanjun Lu (Discover Oncology)
Abstract Long non-coding RNAs (LncRNAs) are crucial regulators of gene expression and cellular processes, with significant implications for cancer research. This review focuses on the role of LncRNA CARMN (Cardiac Arrest and Regulated Myocyte Nuclear Protein) in various cancers. CARMN, originally identified for its function in cardiac tissues, has shown dysregulated expression in several tumor types, including cervical, breast, colorectal, and esophageal cancers. Its altered expression often correlates with tumor progression, metastasis, and patient prognosis, suggesting its potential as both a biomarker and therapeutic target. In cervical cancer, CARMN's role as a tumor suppressor is highlighted by its ability to inhibit cell proliferation, migration, and invasion through interaction with the miR-92a-3p/BTG2 axis and modulation of the Wnt/β-catenin signaling pathway. In breast cancer, CARMN acts as an enhancer RNA, affecting epithelial-mesenchymal transition and metastasis by regulating MMP2 via DHX9. The downregulation of CARMN in triple-negative breast cancer is associated with enhanced sensitivity to chemotherapy. In colorectal cancer, CARMN’s expression is regulated by m6A methylation and mutant p53, influencing tumor growth through miR-5683 and FGF2. Lastly, in esophageal cancer, genetic variations in CARMN affect cancer susceptibility, with certain SNPs and haplotypes associated with either increased or decreased risk. Additionally, the relationship between CARMN and immune cell dynamics highlights its potential role in cancer immune surveillance and therapy. Finally, we found that CARMN may regulate immune cell exhaustion in the tumor microenvironment by influencing the recruitment and activation of NK cells and T cells, as well as modulating macrophage polarization. This review emphasizes the diverse roles of CARMN across different cancers and its potential as a diagnostic and therapeutic tool. Future research should address the mechanistic details of CARMN’s involvement in cancer, validate its clinical utility, and explore its therapeutic potential in combination with existing treatments.